Depression, emotional eating and long-term weight changes: a population-based prospective study - Konttinen, Hanna; van Strien, Tatjana; Männistö, Satu; Jousilahti, Pekka; Haukkala, Ari (The international journal of behavioral nutrition and physical activity, 2019)
Background Emotional eating (i.e. eating in response to negative emotions) has been suggested to be one mechanism linking depression and subsequent development of obesity. However, studies have rarely examined this mediation effect in a prospective setting and its dependence on other factors linked to stress and its management. We used a population-based prospective cohort of adults and aimed to examine 1) whether emotional eating mediated the associations between depression and 7-year change in body mass index (BMI) and waist circumference (WC), and 2) whether gender, age, night sleep duration or physical activity moderated these associations. Methods Participants were Finnish 25- to 74-year-olds who attended the DILGOM study at baseline in 2007 and follow-up in 2014. At baseline ( n = 5024), height, weight and WC were measured in a health examination. At follow-up ( n = 3735), height, weight and WC were based on measured or self-reported information. Depression (Center for Epidemiological Studies - Depression Scale), emotional eating (Three-Factor Eating Questionnaire-R18), physical activity and night sleep duration were self-reported. Age- and gender-adjusted structural equation models with full information maximum likelihood estimator were used in the analyses. Results Depression and emotional eating were positively associated and they both predicted higher 7-year increase in BMI ( R 2 = 0.048) and WC ( R 2 = 0.045). The effects of depression on change in BMI and WC were mediated by emotional eating. Night sleep duration moderated the associations of emotional eating, while age moderated the associations of depression. More specifically, emotional eating predicted higher BMI ( P = 0.007 for the interaction) and WC ( P = 0.026, respectively) gain in shorter sleepers (7 h or less), but not in longer sleepers (9 h or more). Depression predicted higher BMI ( P < 0.001 for the interaction) and WC ( P = 0.065, respectively) increase in younger participants, but not in older participants. Conclusions Our findings offer support for the hypothesis that emotional eating is one behavioural mechanism between depression and development of obesity and abdominal obesity. Moreover, adults with a combination of shorter night sleep duration and higher emotional eating may be particularly vulnerable to weight gain. Future research should examine the clinical significance of our observations by tailoring weight management programs according to these characteristics.